2005
DOI: 10.1111/j.1525-1470.2005.22206.x
|View full text |Cite
|
Sign up to set email alerts
|

X‐linked Reticulate Pigmentary Disorder with Systemic Manifestations: Report of a Third Family and Literature Review

Abstract: Three siblings, two boys and one girl, presented with pigmentary abnormalities. The brothers, ages 11 and 6 years, had diffuse reticulate macular hyperpigmentation with onset in early childhood. In addition, these boys had hypohydrosis, coarse hair with an upswept frontal hairline, failure to thrive, and chronic pulmonary disease. The older boy also had corneal dystrophy and marked photophobia. A punch biopsy specimen from the 11-year-old showed melanophages and necrotic keratinocytes. Stains for amyloid were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 10 publications
2
32
0
Order By: Relevance
“…750 No amyloid has been present, other than in the original report. Occasional apoptotic keratinocytes are also present.…”
Section: Histopathologymentioning
confidence: 59%
See 1 more Smart Citation
“…750 No amyloid has been present, other than in the original report. Occasional apoptotic keratinocytes are also present.…”
Section: Histopathologymentioning
confidence: 59%
“…750 The gene maps to Xp21 near the dystrophin locus. 750 The gene maps to Xp21 near the dystrophin locus.…”
Section: Reticulate Pigmentary Disorder With Systemic Manifestationsmentioning
confidence: 99%
“…as a previously unrecognized X‐linked cutaneous amyloidosis. As it is inherited in an X‐linked pattern, it shows greater severity in males, often causing death 1–3 . Clinically, it manifests with only linear hyperpigmented patches, following Blaschko's lines, in females.…”
Section: Discussionmentioning
confidence: 99%
“…in 1993. Recently, two other families have been described: one in 2005 by Anderson et al 3 . and another in 2008 by Fernandez‐Guarino et al 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Given that many patients require transplantation [2], dermatologists should consider graft versus host disease (GVHD) during a differential diagnosis. In XLRPD, histology essentially reveals the presence of amyloid deposits that are mainly localized within the dermoepidermal junction of adult patients, leading to the hypothesis that this is an age-related condition [3,4,5]. In their report, Pezzani et al [2] described a case of genetically confirmed XLRPD in which no dermopathological symptoms were present at diagnosis.…”
Section: Tablementioning
confidence: 99%